WISP1 Inhibits Hepatocellular Carcinoma Cell Proliferation by Promoting CyclinD1 Ubiquitination and Downregulating its Expression - Yan, Jinlong; Hu, Jun wen; Cheng, Na; Li, Nuoya; Xin, Anqi; Wu, Zhipeng; Wu, Zhengyi; Lei, Jun; Zhang, Shouhua; Yao, Jinping (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma (HCC), a leading cause of cancer-related deaths, is often linked to dysregulated cell cycle proteins. This study focuses on the role of WISP1 in modulating Cyclin D1, a key cell cycle regulator, in HCC. Materials and Methods: The study used HCCLM3 and Hep3B cells to assess the expression of Cyclin D1 and cell proliferation following the treatment of WISP1. This was achieved through Western blot, qRT-PCR, and EdU assays. Additionally, animal studies were conducted to evaluate the effects of WISP1 treatment on Cyclin D1 expression and cell proliferation. Results: Overexpression of WISP1 in HCC cells led to a marked decrease in Cyclin D1 protein levels and reduced cell proliferation. WISP1 influences Cyclin D1 through post-translational modifications, particularly ubiquitination and proteasomal degradation. Conclusion: The findings revealed that WISP1’s modulation of Cyclin D1 plays a critical role in inhibiting HCC cell growth, highlighting a potential therapeutic target for HCC treatment. Cite this article as: Yan J, wen Hu J, Lei J, et al. WISP1 inhibits hepatocellular carcinoma cell proliferation by promoting CyclinD1 ubiquitination and downregulating its expression. Turk J Gastroenterol. 2025;36(4):247-254